Need for appropriate hospital attire in orthopedic patients - Yashpal Gulati; Prince Raina; Y S Suresh Babu (Apollo Medicine)
Introduction: Literature review shows multiple studies on the role of physician attire on patient perceptions. These studies came up with the conclusion that specific dress design might improve the patient-physician bonding. A less likely studied factor in literature was the design of patient attire. The present study aims to design and assess the efficacy of ORTHO dress in orthopedic specialty patients. Patients and Methods: The study population includes 136 patients (62 males and 74 females) presenting to the in-patient department and admitted under orthopedic specialty over 6 months from September 2018 to February 2019 with upper and lower limb illness. The picture-based survey of patient’s preferences regarding choice of attire was conducted on the 3rd day of hospital stay. Results: The mean age of patients was 42.26 ± 10.24 years. The age distribution involves 78 cases (57.35%) were between 15 and 60 years and 58 cases (42.64%) were more than 60 years of age The results show that 124 patients (91.17%) preferred ORTHO dress when dress choice was given when compared with usual hospital dress. Chi-square analysis was used as a test of significance. P < 0.05 was considered statistically significant. Conclusion: Patient attire is the least studied parameter in the medical literature. The influence of specific specialty on patient’s attire is never studied. The ORTHO dress being newly designed and used in orthopedic patients involving upper and lower limb illness plays important role in patient management and has a role in providing better nursing and postoperative rehabilitative care.